Seasonal patterns in energy partitioning of two freshwater marsh ecosystems in the Florida Everglades. Issue 8 (5th August 2014) - Malone, Sparkle L.; Staudhammer, Christina L.; Loescher, Henry W.; Olivas, Paulo; Oberbauer, Steven F.; Ryan, Michael G.; Schedlbauer, Jessica; Starr, Gregory
Abstract We analyzed energy partitioning in short‐ and long‐hydroperiod freshwater marsh ecosystems in the Florida Everglades by examining energy balance components (eddy covariance derived latent energy (LE) and sensible heat (H) flux). The study period included several wet and dry seasons and variable water levels, allowing us to gain better mechanistic information about the control of and changes in marsh hydroperiods. The annual length of inundation is 5 months at the short‐hydroperiod site (25°26′16.5″N, 80°35′40.68″W), whereas the long‐hydroperiod site (25°33′6.72″N, 80°46′57.36″W) is inundated for 12 months annually due to differences in elevation and exposure to surface flow. In the Everglades, surface fluxes feed back to wet season precipitation and affect the magnitude of seasonal change in water levels through water loss as LE (evapotranspiration (ET)). At both sites, annual precipitation was higher than ET (1304 versus 1008 at the short‐hydroperiod site and 1207 versus 1115 mm yr−1 at the long‐hydroperiod site), though there were seasonal differences in the ratio of ET:precipitation. Results also show that energy balance closure was within the range found at other wetland sites (60 to 80%) and was lower when sites were inundated (60 to 70%). Patterns in energy partitioning covaried with hydroperiods and climate, suggesting that shifts in any of these components could disrupt current water and biogeochemical cycles throughout the Everglades region. These results suggest that the complex relationships between hydroperiods, energy exchange, and climate are important for creating conditions sufficient to maintain Everglades ecosystems.